Synthetic essentiality of isoprenylcysteine carboxylmethyltransferase in PTEN deficient triple negative breast cancer - Park, Byung-Sun; Kim, Jaeyeol; Seo, Dong-Chan; Choi, Ga-Eun; Seo, Jin-Ju; Lee, Seung Eun; Kim, Tackhoon (BioMed Central, 2026)
PTEN deficiency is frequently observed in various cancers, including triple-negative breast cancer. However, PTEN loss-of-function mutations are not directly druggable, necessitating a synthetic lethality approach for treating PTEN-deficient tumors. Utilizing combinatorial CRISPR screening, we identified ICMT (isoprenylcysteine carboxylmethyltransferase) loss as synthetic lethal with PTEN deficiency. Genetic or pharmacological inhibition of ICMT effectively reversed cellular transformation induced by PTEN loss. Mechanistically, ICMT loss disrupts the positive feedback loop involving PIP3-PIP3-dependent guanine nucleotide exchange factor (GEF)-Rac1-PI3K by increased physical association of Rac1 and RhoGDI, inhibiting Rac1 activity and stability. Disruption of this feedback loop attenuates epithelial-mesenchymal transition and reduces the cancer stem cell population. Additionally, ICMT loss leads to the accumulation of aggregated proteins, which activates the unfolded protein response (UPR) signaling, ultimately resulting in cell death. Cysmethynil, an ICMT inhibitor, effectively suppresses PTEN-mutant cancer growth in xenograft models. Collectively, our study establishes ICMT as a promising therapeutic target for treating PTEN-mutant cancers.